Take-off control and characteristics of FanWing. Issue 5 (28th December 2021) - Meng, Lin; Gao, Yang; Liu, Yangyang; Lu, Shengfang
Abstract : Purpose: As a short take-off and landing aircraft, FanWing has the capability of being driven under power a short distance from a parking space to the take-off area. The purpose of this paper is to design the take-off control system of FanWing and study the factors that influence the short take-off performance under control. Design/methodology/approach: The force analysis of FanWing is studied in the take-off phase. Two take-off control methods are researched, and several factors that influence the short take-off performance are studied under control. Findings: The elevator and fan wing control systems are designed. Although the vehicle load increases under the fan wing control, the fan wing control is not a recommended practice in the take-off phase for its sensitivity to the pitch angle command. The additional pitch-down moment has a significant influence on the control system and the short take-off performance that the barycenter variation of FanWing should be considered carefully. Practical implications: The presented efforts provide a reference for the location of the center of gravity in designing FanWing. The traditional elevator control is more recommended than the fan wing control in the take-off phase. Originality/value: This paper offers a valuable reference on the control system design of FanWing. It also proves that there is an additional pith-down moment that needs to be paid close attention to. Four factors that influence the short take-off performance are compared under control.